Multimodal approach to human detection in unconstrained environments using YOLOV7 for conventional, infrared & thermal cameras - Rukaiya, Maymuna; Khan Soumik, Md. Muhtadee Faiaz; Sakib, Sazzad Hossan; Islam, Md. Ashikul; Ishrak, Mohammad Farhan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.